2012
DOI: 10.1097/qad.0b013e328350995c
|View full text |Cite
|
Sign up to set email alerts
|

A national review of vertical HIV transmission

Abstract: Vertical HIV transmission in Canada has decreased dramatically for women treated with HAART therapy. All pregnant women should be evaluated for HIV infection and programmes expanded to reach vulnerable populations including aboriginal, immigrant and IDU women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
87
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(93 citation statements)
references
References 17 publications
3
87
2
1
Order By: Relevance
“…of successful treatment with combination antiretroviral therapy (cART) resulting in undetectable viral loads and vertical transmission rates being less than 1% (Chen, Phillips, Kanouse, Collins, & Miu, 2001;Cooper et al, 2002;Forbes et al, 2012). In fact, the Public Health Agency of Canada reported that in 2012, 94.2% of WLWH received cART in pregnancy resulting in no identified HIV transmissions to infants despite exposure to HIV during the perinatal period (Public Health Agency of Canada [PHAC], 2013).…”
mentioning
confidence: 96%
“…of successful treatment with combination antiretroviral therapy (cART) resulting in undetectable viral loads and vertical transmission rates being less than 1% (Chen, Phillips, Kanouse, Collins, & Miu, 2001;Cooper et al, 2002;Forbes et al, 2012). In fact, the Public Health Agency of Canada reported that in 2012, 94.2% of WLWH received cART in pregnancy resulting in no identified HIV transmissions to infants despite exposure to HIV during the perinatal period (Public Health Agency of Canada [PHAC], 2013).…”
mentioning
confidence: 96%
“…Since 2013 a rapid shift to PMTCT Option B+ has occurred, and 18 of the 22 Global Plan priority countries (countries that house >90% of the world' s population of pregnant HIV positive women) have either endorsed, implemented or conducted national scale-up of PMTCT Option B+ [9]. "B+" has reduced final MTCT to <2% in nonbreastfeeding countries [10]. Between 2001 and 2010, in resource-limited, high HIV prevalence countries, such as South Africa, rigorous routine measurements of national PMTCT impact and trends were simply unavailable.…”
mentioning
confidence: 99%
“…In AIDS, the immune system is inhibited by the virus, which makes patients have more opportunities for deadly infections and cancers. The HIV virus is transmitted via unprotected sexual intercourse [5, 6], contaminated medical equipment [7, 8], bodily fluids, and vertical infection (pregnancy, delivery, or breastfeeding) [9, 10]. …”
Section: Introductionmentioning
confidence: 99%